Coding variants of TLR2 and TLR4 genes do not substantially contribute to prosthetic joint infection - Mrazek, Frantisek; Gallo, Jiri; Stahelova, Anna; Petrek, Martin (Inflammation research, 2013)
OBJECTIVE AND DESIGN: Prosthetic joint infection (PJI) is a severe complication of total joint arthroplasty (TJA). We conducted a genetic association study that investigated whether selected coding variants of the genes for Toll-like receptors (TLR)2 and TLR4 may contribute to genetic susceptibility for PJI. SUBJECTS AND METHODS: In total, 350 patients with TJA (98 with PJI/252 without PJI), and 189 unrelated healthy Czech individuals without TJA were enrolled in our study. Three missense polymorphisms of the genes encoding for TLR2 (TLR2 R753Q, rs5743708) and TLR4 (TLR4 D299G, rs4986790 and T399I, rs4986791) were genotyped by "TaqMan" assay. RESULTS: The frequencies of less common variants for the investigated TLR2/TLR4 polymorphisms in healthy individuals were similar to those observed in other Caucasian populations. Importantly, the distribution of TLR2/TLR4 genotype alleles did not differ between the patients with PJI and the control groups of patients with nonseptic prostheses/healthy individuals. CONCLUSION: Our data suggest that structural genetic variants of the receptors TLR2 and TLR4 do not substantially affect the risk of prosthetic joint infection.
Keywords: Arthroplasty; Female; Toll-Like Receptor 2; Prostheses and Implants; ženské pohlaví; jednonukleotidový polymorfismus; toll-like receptor 4; infekce spojené s protézou; lidé; Staphylococcus; infekce; Polymorphism, Single Nucleotide; Prosthesis-Related Infections; klouby; Infections; artroplastika; stafylokokové infekce; toll-like receptor 2; Joints; Male; Aged; Toll-Like Receptor 4; lidé středního věku; Staphylococcal Infections; protézy a implantáty; senioři; mužské pohlaví; Middle Aged; Humans